The impact of the economic crisis on Italian young people's everyday life - Mortara,Ariela (2015)
In Italy, the economic crisis of the last years has been characterized by recession, deflation, and unemployment. In addition to its broader effect on society, the crisis has deeply affected Italians'!everyday practices, their views, and their future goals. This is particularly true for young people, who can no longer rely on rising expectations. The paper presents the preliminary results of a qualitative study aimed at understanding how young people perceive and handle their everyday life in a social and working context so heavily influenced by income uncertainty, job insecurity, and a general lack of confidence in the future. Face-to-face in-depth interviews have been conducted in the metropolitan area of Milan (Italy)